Effect of Parents’ Encouragement on Reading Motivation: The Mediating Effect of Reading Self-Concept and the Moderating Effect of Gender - Xia, Tiansheng; Gu, Honglei; Li, Weirong (Frontiers in Psychology, 2019)
Previous research has found that parental encouragement is associated with children’s motivation to read. However, little is known about the underlying mechanisms of this association or factors that might strengthen or weaken these processes. The current research scrutinized a moderated mediation model that comprised of parental encouragement (predictor variable), reading self-concept (mediator), gender (moderator), and reading motivation (outcome variable) simultaneously. A total of 254 Chinese students (Mage = 11.35 years, SDage = 0.87) completed the Parents’ Encouragement of Extracurricular Reading Questionnaire, Reading Self-Concept Scale, and Pupil Reading Motivation Scale. Path analysis revealed that parents’ encouragement was associated with children’s reading motivation both directly and indirectly via reading self-concept, and the effect of parents’ encouragement on children’s motivation was more positive for boys than girls, while the effect of reading self-concept on children’s motivation was more positive for girls than boys. Our results highlight the importance of parental encouragement in improving children’s reading motivation, and the findings and their implications are discussed.